On central limit theorem for sums of series weakly dependent random variables - Riauba, B. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Ряуба, О центральной предельной теореме для сумм серий слабо зависимых случайных величин B. Riauba, Dėl centrinės ribinės teoremos silpnai priklausomų atsitiktinių dydžių serijų sumoms